2019
DOI: 10.1080/22797254.2019.1658542
|View full text |Cite
|
Sign up to set email alerts
|

Shallow water bathymetry from WorldView-2 stereo imagery using two-media photogrammetry

Abstract: Two-media photogrammetry appears to be a useful technology for mapping shallow water depth. The objective of this paper is to explore the feasibility of shallow water bathymetry using satellite two-media photogrammetry. This paper presents a two-media photogrammetry technique for WorldView-2 stereo multispectral imagery. In this method, near-infrared band is used for sun glint elimination. A combination of Scale Invariant Feature Transform and Semi-Global Matching algorithm is adopted for dense stereo matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 24 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Based on the WorldView-2 high resolution multispectral images, a new empirical model for shallow water depth bathymetry is proposed. Similarly, many other methods have also been developed using WorldView-2 data, such as a two-media photogrammetry technique for WorldView-2 stereo multispectral imagery proposed by Cao et al [35]. The research areas selected in the article are also located in the Paracel Islands (Zhaoshu Island and Ganquan Island) in the South China Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the WorldView-2 high resolution multispectral images, a new empirical model for shallow water depth bathymetry is proposed. Similarly, many other methods have also been developed using WorldView-2 data, such as a two-media photogrammetry technique for WorldView-2 stereo multispectral imagery proposed by Cao et al [35]. The research areas selected in the article are also located in the Paracel Islands (Zhaoshu Island and Ganquan Island) in the South China Sea.…”
Section: Discussionmentioning
confidence: 99%
“…The SIFT algorithm is used to provide accurate local feature points for correcting wrong disparities in weak texture or occluded areas, generated by the SGM algorithm. Cao et al described the detailed procedure of the combined algorithms, and showed the practical performance [47].…”
Section: ) Bathymetric Retrieval Algorithm Based On Multi-angular Immentioning
confidence: 99%
“…Another approach which utilizes satellite imagery is two-media photogrammetry, which is a method that has been around for a long time [3,4]. In recent years, WordView-2 stereo imagery has been used to derive bathymetry estimates for depths ranging between 5 and 20 m with Root Mean Square Errors (RMSE) around 1-2 m [5,6]. In addition to satellite imagery, air-borne or even images from drones can be used to derive shallow water bathymetry.…”
Section: Introductionmentioning
confidence: 99%